Damage Evolution of Sandstone under Constant-Amplitude Cyclic Loading Based on Acoustic Emission Parameters and Resistivity - Kui Wang; Zhengting Xia; Zhen Huang; Xue Li (Advances in Materials Science and Engineering)
In the real environment, besides static load, rock is more affected by cyclic load. There is a large difference in the mechanical properties exhibited by rocks under cyclic and static loading. Therefore, it is particularly necessary to investigate the mechanical characteristics of rock subjected to cyclic loading. These parameters of rock, acoustic emission (AE) and resistivity, are both sensitive to the failure process of rock, and they are complementary to the different stages of rock damage. Therefore, in this paper, the AE characteristics and resistivity properties of sandstone subjected to constant-amplitude cyclic loading and unloading were experimentally investigated using a typical sandstone in Chongqing. The same three-stage pattern was found for the AE evolution of sandstones during constant-amplitude cyclic loading. Initial evolution stage: the rock deformation is fast with strong changes in the AE signal. The rock deformation developed slowly while the changes of the AE signal were stable in the constant velocity evolution stage. The rock deformation developed dramatically while the AE signal became more intense in accelerated evolution stage. The change in resistivity is characterized by a rapid decrease during the loading stage and a rapid rebound during the unloading stage. Overall, from the beginning of the cycle to the end of the cycle, the resistivity of the sandstone showed a general trend of gradual decrease, until the sudden increase in resistivity at the time of damage. Finally, a damage model based on AE parameters and resistivity was constructed by combining damage mechanics.